Jawabanmu

2014-03-19T17:58:19+07:00
U1 = a
u2 = a+b
u3 = a+2b
u1+u2+u3 = 42
a+a+b+a+2b = 42
3a+3b = 42
a+b = 14
b=14-a

u1.u2.u3= 2520
(a)(a+b)(a+2b) = 2520
a.14.(a+2(14-a)) = 2520
a(a+28-2a) = 180
a(28-a)=180
-a^2+28a=180
-a^2+28a-180=0
(-a+18)(a-10)= 0
a= 10  -----> U1 = 10
Smoga membantu
2014-03-19T18:57:05+07:00
U1 = a+(n-1)b
    = a+(1-1)b
    = a
u2 = a+(n-1)b
     = a+(2-1)b
     = a+b
u3 = a+(n-1)b
    = a+(3-1)b
     = a+2b
u1+u2+u3 = 42
a+a+b+a+2b = 42
3a +3b = 42
3b = 42-3a
b = (42-3a)/3
b = 14 - a

u1*u2*u3 = 2520
a*(a+b)*(a+2b) = 2520
a*(a+14-a)*(a+2(14-a)) = 2520
a*14*(a+28-2a) = 2520
14a(28-a) = 2520
392a-14a² = 2520
14(28a-a²)=2520
28a - a² = 180
Dicoba ⇒ a=10
maka,
28a -a² = 180
28*10-(10*10)=180
280-100=180
180=180

JADI u1 = 10